Factors Influencing the Adoption of Clinical Informatics Tools among Medical Doctors in South Africa - Abayomi, Owolabi Kehinde; D., Neils Evan; Ajao, Aderibigbe Nurudeen (Journal of Information and Knowledge, 2020)
The adoption of clinical informatics tools has been very poor in many developing countries and a better understanding of the factors that influence clinical informatics integration is expected to promote the effective utilisation of its tools. To shed more light on this phenomenon, the study employed the use of Universal Theory of Acceptance and Use of Technology (UTAUT) to identify the factors that influence the use of clinical informatics tools. The study employed a positivism research paradigm anchored on survey research design. Simple random sampling technique was used to select one hundred and five medical doctors in a tertiary hospital in South Africa. Data were collected with the use of a structured questionnaire. Structural equation modelling was used to analyse the data collected. Findings from the study revealed that facilitating condition was not related to behavioural intention to use clinical informatics (β = 0.09, p>0.05), effort expectancy was related to behavioural intention to use clinical informatics (β = 0.41, p<0.05), performance expectancy was related to behavioural intention to use clinical informatics (β = 0.47, p<0.01) and social influence was not related to behavioural intention to use clinical informatics (β = -0.11, p>0.05). The study therefore recommends the need for the hospital management to create conducive environment that will promote effective use of clinical informatics make clinical information tools more user friendly and organise training programmes for effective use of the tools.. The study contributes to debates and discussions on UTAUT theory. The evidence from the study will help to identify the factors that influence behavioural intention towards the use of clinical informatics tools, which will provide a strong opportunity for a better understanding of factors that can motivate medical doctors to use clinical informatics effectively.